Bone status in young women with rheumatic diseases - O. V. Dobrovolskaya; N. V. Demin; A. V. Smirnov; L. A. Shornikova; O. A. Nikitinskaya; N. V. Toroptsova (Научно-практическая ревматология)
Objective: to investigate bone mineral density (BMD) status and the factors influencing the latter in reproductive-aged women with rheumatic diseases (RDs).Subjects and methods. The investigation enrolled 134 women (mean age, 35 [29; 43] years): 94 patients with RDs (rheumatoid arthritis (RA), systemic sclerosis (SS), and psoriatic arthritis (PsA)) and 40 people without RDs. The investigators conducted a survey using a unified questionnaire, spine and proximal femur bone densitometry by dual energy X-ray absorptiometry (Hologic Discovery A Bone densitometer, USA), serum vitamin D measurement, and daily dietary calcium intake estimation.Results and discussion. Reduced BMD was detected significantly more often in the group of patients with RDs compared with the healthy control (25 and 8%, respectively; p=0.0213). It occurred in 48% of patients with RA, in 21% of those with SS, and in 15% of those with PsA. Patients with RDs showed a direct correlation of BMD in all areas of measurement with height, weight, body mass index, and serum vitamin D concentration and an inverse correlation with the cumulative dose of glucocorticoids. In addition, an inverse correlation was found between proximal femur BMD and RD duration. The patients with SS displayed an inverse relationship between BMD of both proximal femurs and C-reactive protein level; and the women with RA had exhibited this relationship between lumbar spine and femoral neck BMD and ESR.Conclusion. In general, 25% of reproductive-aged women with RDs need osteoporosis monitoring and prevention, and, in the presence of fractures, antiosteoporotic treatment.